2019
DOI: 10.1029/2018wr023679
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Automata Fast Flood Evaluation (CA‐ffé) Model

Abstract: The simulation speed of two-dimensional hydrodynamic flood models is a limiting factor when catchments are large, a considerable number of simulations is required (e.g., exploratory modeling, Monte-Carlo flood simulations, or predicting probabilistic flood maps), or when there is a need for real-time flood emergency management. Rapid Flood Models (RFMs) that rely only on topographic depressions and the water balance equation have been successfully implemented to predict maximum urban flood inundation depths wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Among the shortcomings of flow simulation models in the studies conducted by Tavakolifar et al (2021), Abbasizadeh et al (2017) and Jamali et al (2019), one can mention the inability of these models in modeling the effects of permeability of the study area at the flood volume and flow simulation. This makes these models not capable of modeling changes in the flow status and permeability amount of catchment due to the use of BMPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the shortcomings of flow simulation models in the studies conducted by Tavakolifar et al (2021), Abbasizadeh et al (2017) and Jamali et al (2019), one can mention the inability of these models in modeling the effects of permeability of the study area at the flood volume and flow simulation. This makes these models not capable of modeling changes in the flow status and permeability amount of catchment due to the use of BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the CA method requires less computational time to model the flow than other ones, which use 2D flow motion equations. Using the CA theory, Jamali et al (2019) modelled floods in urban areas and compared the results with those via 2D ones. This comparison illustrated that the proposed CA-based model results in higher flood wave speed than the 2D models.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of computational speed and deterministic nature of the HD models had led researchers to redirect their efforts toward alternatives. One of the promising techniques is the use of data‐driven models (e.g., Berkhahn et al, 2019; Bermúdez et al, 2018, 2019; Jamali et al, 2018; 2019; Jato‐Espino et al, 2018; Jhong et al, 2017; Schultz et al, 2006; Solomatine & Ostfeld, 2008; Vojinovic & Seyoum, 2008; Wolfs & Willems, 2016). Ranging from employing statistical methods to employing artificial intelligence methods, data‐driven models are good at capturing the nonlinear input‐output response surface of the input‐output data sets (Razavi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It can be classified as "finite volume" implementation [18] because it discretizes the spatial domain into control volumes (e.g., regular 2D cells). Previous studies and models on the basis of CA proved its accuracy in modeling hydraulic processes and its computational efficiency [33][34][35][36]. CA models behave like diffusive wave-like models [35] by neglecting the conservation of momentum.…”
Section: Introductionmentioning
confidence: 99%